IMPROVING TAX ADMINISTRATION IN UZBEKISTAN - Nargiza Kasimova (European Science Publishing, 2024)
This article examines the development and modernization of tax administration in Uzbekistan, emphasizing its importance in enhancing fiscal efficiency, transparency, and economic growth. The study highlights the role of advanced technologies, simplified procedures, and institutional reforms in improving the effectiveness of tax collection and compliance. It also discusses the challenges associated with the current tax system and offers recommendations for aligning tax administration practices with international standards. By exploring the ongoing reforms in Uzbekistan, the article sheds light on the potential of an optimized tax administration system to support sustainable economic development.
Keywords: Tax administration, fiscal policy, economic growth, tax reforms, Uzbekistan, transparency.